Living waste, living on waste: a bioeconomy of urban cows in Delhi - Turnbull, J; Barua, M (Wiley, 2022)
The economic implications of biopolitics – or the administration, regulation, and control of life – have received significant attention in recent geographical and cognate scholarship. An emerging theme of inquiry, largely focused on the Global North, makes contributions to specifying ‘lively capital’, defined here as bodily value in motion – predicated on accumulation from other-than-human life. In this paper, we argue that the biopolitical process of bringing life into the ambit of capital works in cultural, political, and economic registers and not just through singular logics of the economic, as extant accounts have implied. The rendition of life into capital through modes of biopower is not a universal process. It has diverging trajectories that, in postcolonial contexts, involve hybrids between biopolitical and vernacular practices. This argument is made through an account of bovine biopolitics in urban Delhi with specific reference to the city's ‘cattle problem’ involving ‘surplus’ animals. It unfolds in four distinct parts. First, drawing on archival work, we trace colonial histories of cattle improvement to reveal how the category of ‘surplus’ was invented. Second, we deploy more-than-human ethnographies of free-ranging animals in Delhi to foreground how ‘surplus’ cattle – which we conceptualise as ‘living waste’ – are driven to feed on waste as a result of gentrification and the enclosure of erstwhile grazing grounds. Third, we turn to gaushalas (cow shelters) in Delhi to show how ‘surplus’ cattle from the city's streets are rehomed and managed. Fourth, we examine the uneven practices of care afforded to different bovines based on logics associated with right-wing Hindutva nationalism. Our account provincialises lively capital by opening up more nuanced and situated understandings of the relations between biopolitics and capitalism, attentive to divergences from models situated in Western modernity.